2008
DOI: 10.1097/ccm.0b013e3181692dfc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age of transfused blood on cerebral oxygenation in male patients with severe traumatic brain injury*

Abstract: Transfusion of erythrocytes increased cerebral oxygenation in patients with severe traumatic brain injury, except in those transfused with erythrocytes stored >19 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
141
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 21 publications
6
141
3
1
Order By: Relevance
“…The authors report that: "There was a significant short-lasting (3-4 hrs) increase in pbtO2 values after transfusion of erythrocytes stored for <10 days, 10-14 days, or 15-19 days, compared with those at baseline. In contrast, no significant changes in pbtO2 were observed after transfusion of erythrocytes stored >19 days" [136]. Similar findings have been confirmed elsewhere in an animal study [135].…”
Section: Anemiasupporting
confidence: 75%
See 1 more Smart Citation
“…The authors report that: "There was a significant short-lasting (3-4 hrs) increase in pbtO2 values after transfusion of erythrocytes stored for <10 days, 10-14 days, or 15-19 days, compared with those at baseline. In contrast, no significant changes in pbtO2 were observed after transfusion of erythrocytes stored >19 days" [136]. Similar findings have been confirmed elsewhere in an animal study [135].…”
Section: Anemiasupporting
confidence: 75%
“…The aspect of storage duration of RPBC on the effects of pbtO2 has been studied in 66 anaemic male TBI patients [136]. The authors report that: "There was a significant short-lasting (3-4 hrs) increase in pbtO2 values after transfusion of erythrocytes stored for <10 days, 10-14 days, or 15-19 days, compared with those at baseline.…”
Section: Anemiamentioning
confidence: 91%
“…Three months later, Leal-Noval and his colleagues reported on a study of transfusion in brain-injured patients with brain tissue oxygen electrodes implanted in the side contralateral to the injury [56]. They reported that BtPO 2 did not improve in male patients after transfusion of red blood cell units stored longer than 19 days.…”
Section: Data From Clinical Studiesmentioning
confidence: 99%
“…10 Despite that, universal blood transfusion triggers continue to be controversial, and there is evidence to suggest that "dosing" blood by unit(s) as opposed to absolute hematocrit targets may be more prudent in the context of brain tissue oxygenation. [11][12][13] The age of the transfused blood may also be an important consideration, with more favorable cerebral oxygenation responses seen following transfusions of blood stored for fewer than 19 days. 11 Therapy directed at correcting hypovolemic shock includes prompt volume expansion with crystalloid solutions, followed by administration of blood products as per established trauma guidelines.…”
mentioning
confidence: 99%
“…[11][12][13] The age of the transfused blood may also be an important consideration, with more favorable cerebral oxygenation responses seen following transfusions of blood stored for fewer than 19 days. 11 Therapy directed at correcting hypovolemic shock includes prompt volume expansion with crystalloid solutions, followed by administration of blood products as per established trauma guidelines. It is hypothesized that, following traumatic brain injury, cerebrovascular dysfunction results in loss of brain compliance, resulting in increased sensitivity to elevated venous pressures.…”
mentioning
confidence: 99%